2020
DOI: 10.1002/anie.201915416
|View full text |Cite
|
Sign up to set email alerts
|

Small‐Molecule Modulation of Soft‐Matter Frank–Kasper Phases: A Method for Adding Function to Form

Abstract: Incorporation of small amounts of α‐tocopherol (vitamin E) in blends with the cellobiose–triazole‐linked atactic poly(4‐methyl‐1‐pentene) (CB‐aPMP) sugar–polyolefin conjugate can be used to exert external control over thermotropic phase behavior and provide access to non‐canonical soft matter Frank–Kasper A15 and σ phases. These results establish a paradigm that can be used for the further design and development of scalable quantities of soft matter FK phases of increased structural complexity and functional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…Importantly, all BCPs exhibited an intense principal scattering ( q *) along with multiple higher ordered scattering peaks, which is an indication of microphase separation between the PDL and oligosaccharide segments. The strong hydrophilicity and conformation rigidity of the maltooligosaccharide segments render them highly incompatible to the hydrophobic PDL, which enables the microphase separation in spite of the small f sac and the relatively low molecular weights. Specifically, the SAXS profiles of Glc 6 - b -PDL- b -Glc 6 after the thermal annealing revealed the formation of the body-centered-cubic sphere (BCC) morphology, as evidenced by the characteristic scattering pattern of q / q * = 1, √2, √3, 2, and so on (Figure a). The intersphere distance ( d s‑s ) value of the BCC structures was calculated to be 13.6 nm based on the Bragg equation ( d s‑s = (2π/ q *)­(3/2) 1/2 ).…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, all BCPs exhibited an intense principal scattering ( q *) along with multiple higher ordered scattering peaks, which is an indication of microphase separation between the PDL and oligosaccharide segments. The strong hydrophilicity and conformation rigidity of the maltooligosaccharide segments render them highly incompatible to the hydrophobic PDL, which enables the microphase separation in spite of the small f sac and the relatively low molecular weights. Specifically, the SAXS profiles of Glc 6 - b -PDL- b -Glc 6 after the thermal annealing revealed the formation of the body-centered-cubic sphere (BCC) morphology, as evidenced by the characteristic scattering pattern of q / q * = 1, √2, √3, 2, and so on (Figure a). The intersphere distance ( d s‑s ) value of the BCC structures was calculated to be 13.6 nm based on the Bragg equation ( d s‑s = (2π/ q *)­(3/2) 1/2 ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…10,11 It should be noted here that previous studies by our group and Sita's group revealed that block copolymers (BCPs) consisting of hydrophobic polymers and oligosaccharides readily self-assembled into microphase-separated structures due to the strong segregation between the blocks, which was further enhanced by the rigid rod nature of the oligosaccharide. [12][13][14][15][16][17][18][19][20][21][22][23] We therefore envisioned that the integration of a rubbery hydrophobic polymer at the middle block and oligo/polysaccharide hard segments at the outer blocks could provide a novel bio-based elastomer, in which the microphase-separated carbohydrate hard domains act as a physical crosslink for the rubbery chains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Scheme reveals, at the core of LCCTP is a dynamic reversible polymeryl group transfer process that occurs between a small population of transition-metal active sites derived from 1 upon “activation” using a stoichiometric amount of a borate co-initiator, such as [PhNH­(Me) 2 ]­[B­(C 6 F 5 ) 4 ], and a much larger population of “surrogate” main-group-metal chain-growth centers derived from an excess (relative to 1 ) of a relatively inexpensive commodity main-group-metal alkyl, such as diethylzinc, ZnEt 2 (DEZ), triethylaluminum, AlEt 3 (TEAL), or mixtures of the two. , If the rate constant for reversible chain transfer, ν CT ( k CT ), is much larger than the rate constant for propagation, ν p ( k p ), then the populations of active and surrogate sites will appear to propagate at the same rate with the final degree of polymerization being defined by DP n = {[monomer] 0 – [monomer] t }/([(M A – P A ) + + n (M′ B – P B )] 0 ), where n is the number of equivalent polymeryl groups per main-group metal (e.g., n = 2 for DEZ) and Đ ≈ 1 + k p / k CT . Another advantage of LCCTP over traditional LCP is that the final main-group-metal polymeryl product can be further functionalized to produce poly­(α-olefinates) ( x PAOs) products through simple chemical transformations involving the reactive Zn–C (or Al–C) bonds …”
Section: Introductionmentioning
confidence: 99%
“…The original self-assembling compounds were constructed from benzyl ether dendrons functionalized with aliphatic, fluorinated, semifluorinated, and oligooxyethylene fragments , and subsequently were expanded to other constructs to be discussed in more detail later. They led to the immediate discovery of helical self-organizations, Frank–Kasper phases, and soft quasicrystals that were subsequently found in many other forms of soft matter such as block copolymers, lipids, surfactants, giant molecules, and DNA-grafted nanoparticles. More recently they evolved in biological membrane mimics and into a single component delivery system for mRNA . The dream of self-organized complex soft matter is to reach the perfection of periodic arrays self-organized from inorganic materials that are assembled from a small number of atoms as well as that of biological macromolecules that is self-organized from millions of atoms.…”
Section: Introductionmentioning
confidence: 99%